Draft double taxation convention on income and capital; [report. - Organization for Economic Cooperation and Development (Paris: Organisation for Economic Co-operation and Development, 1963)
This 1963 report presents the articles on the avoidance of double taxation on income and capital, as agreed upon by the Fiscal Committee. Double taxation is the taxation of a single taxpayer with respect to the same subject matter over the same period in more than one country. This draft aims to inspire further conventions on the elimination of double taxation, a threat to trade and migration. The report includes commentaries on the articles, progress on the elimination of double taxation, and possible future developments.
obn 22/01/2019
Loans
Keywords: Double taxation; Income; Capital